The Role of Explicit Knowledge, Noticing, and Attention in L2 Writing and Error Correction: Quantitative and Qualitative Analyses (JOURNAL OF ADVANCES IN LINGUISTICS, 2014)
This study attempted to find answers for the following questions: (1) Are students errors in grammatical structures, as they will appear in their written output, due to deficiency in their conscious grammar rules, or to deficiency in their abilities to transfer this knowledge (if it exists) to other language tasks such as writing compositions in English?, and (2) Can conscious rules of grammar guide students' performance in monitoring (self-correcting) their written output once their attention is drawn to an error?.  The subjects of this study consisted of fifteen foreign students enrolled in the advanced level of the English Language Institute at the University of Pittsburgh. The instruments of this study were (1) questionnaire; (2) free composition; (3) unfocused correction and focused correction tasks; and (4) interviews.  The results of this study demonstrate, among other things, that deficiency in the subjects knowledge of grammar results in accurate composition writing and unsuccessful correction of errors, even if their attention is drawn to their errors.